2011
DOI: 10.1080/10937404.2011.556047
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Endpoints (Lung Carcinomas and Asbestosis) Following Inhalation Exposure to Asbestos

Abstract: Lung carcinomas and pulmonary fibrosis (asbestosis) occur in asbestos workers. Understanding the pathogenesis of these diseases is complicated because of potential confounding factors, such as smoking, which is not a risk factor in mesothelioma. The modes of action (MOA) of various types of asbestos in the development of lung cancers, asbestosis, and mesotheliomas appear to be different. Moreover, asbestos fibers may act differentially at various stages of these diseases, and have different potencies as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
165
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 215 publications
(326 reference statements)
3
165
0
2
Order By: Relevance
“…Potential effects of airborne fibers in humans can only occur after a complex www.intechopen.com process of inhalation, deposition, elimination, retention and translocation. The biological effects of inhaled fibers are highly dependent on dose (fiber exposure concentrationnumbers of long fibers), fiber size (diameter/length), (Donaldson & Tran, 2004;Kohyama et al, 1997;Yamato et al, 1998), durability of material in the organism (biopersistence) (Mossman et al, (2011), duration of exposure, chemical composition and properties, solubility, chemical reactivity, surface properties of the material, ability of a material to interact with body proteins etc. Host factors such as efficiency of defense mechanisms of the respiratory tract between the initial deposition and the ultimate contact of the fibers with the target cell, individual susceptibility to xenobiotics, metabolism, age, nutrition status, life style (smoking), presence of immune disease (asthma, allergic rhinitis, immunosuppression etc.)…”
Section: Hazard Assessment Of Mineral Fibers and Particlesmentioning
confidence: 99%
“…Potential effects of airborne fibers in humans can only occur after a complex www.intechopen.com process of inhalation, deposition, elimination, retention and translocation. The biological effects of inhaled fibers are highly dependent on dose (fiber exposure concentrationnumbers of long fibers), fiber size (diameter/length), (Donaldson & Tran, 2004;Kohyama et al, 1997;Yamato et al, 1998), durability of material in the organism (biopersistence) (Mossman et al, (2011), duration of exposure, chemical composition and properties, solubility, chemical reactivity, surface properties of the material, ability of a material to interact with body proteins etc. Host factors such as efficiency of defense mechanisms of the respiratory tract between the initial deposition and the ultimate contact of the fibers with the target cell, individual susceptibility to xenobiotics, metabolism, age, nutrition status, life style (smoking), presence of immune disease (asthma, allergic rhinitis, immunosuppression etc.)…”
Section: Hazard Assessment Of Mineral Fibers and Particlesmentioning
confidence: 99%
“…These tissue samples were obtained from cases throughout the United States that were sent to Dr. Suzuki for pathological review and were systematically analyzed using histology, immunohistochemistry, and electron microscopy, in some cases, over a 15-yr period. As summarized succinctly by Dumortier et al (1998) in a letter to the editor in 1998, the size and type of asbestos fibers associated with development of diffuse malignant pleural mesothelioma remain controversial (Mossman et al, 2011;Case et al, 2011;Aust et al, 2011).One possible explanation for the confusion in pleural sampling came from a pioneering study carried out by Boutin et al (1996). Using video-assisted fiber-optic thoracoscopy in eight asbestos-exposed patients and six unexposed cases, Dr. Boutin and colleagues (1996) sampled specific anatomic regions of the parietal pleura identified as collecting spots for inorganic particulates and fibers that (1996) identified numerous amphibole as well as chrysotile fibers at black spots, and 22.5% were ≥5 μm long.…”
mentioning
confidence: 99%
“…(Ghio et al, 2008). In response to chronic oxidative stress, intracellular signaling pathways trigger activation of transcription factors, stimulation of cell proliferation, and resistance to apoptosis (Albrecht et al, 2004;Mossman et al, 2011).Asbestos in cell culture (Broaddus et al, 1996; Berube et al, 1996) and in some animal studies (Marchi et al, 2000) was found to induce apoptosis in mesothelial cells, and ROS may contribute to this early apoptosis (Broaddus et al, 1996); at later times, DNA or chromosomal damage may also trigger apoptosis. Presumably, it is the cells that have inherent resistance to apoptosis or acquire resistance that will survive the initial and ongoing damage to initiate multistep acquisition of genetic abnormalities that characterize tumor development (Broaddus, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [15,42,43] [28]. The toxicology of chrysotile, such as tremolite asbestos, is associated with size, durability, and chemical composition [27,44,45].…”
Section: Introductionmentioning
confidence: 99%